1981
DOI: 10.1002/1097-0142(19810301)47:5<930::aid-cncr2820470519>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of histologic host response in cancer of the large bowel

Abstract: Histologic material from 156 patients treated with surgery for cancer of the large bowel was studied with regard to tumor host interaction and with particular emphasis on the reactions of the regional lymph nodes. Prognostic evaluation of the tumor included the extent of the primary lesion according to Dukes' classification and the grade of differentiation of the carcinoma. Morphologic evidence of host resistance was judged by the presence and degree of lymphoplasmacytic infiltration of the tumor and the react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Patients with histologic evidence of a more vigorous immune response experience improved outcomes 37,38 . Similarly, patients with a depleted or under-stimulated lymphocytic response to their crc, either within their lymphatics 39 or at the tumour edge 40 , have a relatively unfavourable prognosis. Galon et al 41 coined the term "immune contexture" to describe the effect of the local host immune reaction in crc.…”
Section: Discussionmentioning
confidence: 67%
“…Patients with histologic evidence of a more vigorous immune response experience improved outcomes 37,38 . Similarly, patients with a depleted or under-stimulated lymphocytic response to their crc, either within their lymphatics 39 or at the tumour edge 40 , have a relatively unfavourable prognosis. Galon et al 41 coined the term "immune contexture" to describe the effect of the local host immune reaction in crc.…”
Section: Discussionmentioning
confidence: 67%
“…They studied that majority of well and moderately differentiated tumors were of stage II, whereas maximum proportion of poorly differentiated tumors had stage III. Similarly Ueno et al, Nacopoulou et al and Vasile et al [13,38,39] also confirmed the poor survival of high-grade tumors. Spratt et al [21] evaluated that survival of patients with colorectal carcinoma is related to lymphocytic response, as more the lymphocytic response better is the survival of patient.…”
Section: Resultsmentioning
confidence: 99%
“…Spratt et al [21] evaluated that survival of patients with colorectal carcinoma is related to lymphocytic response, as more the lymphocytic response better is the survival of patient. Also Nacopoulou et al [38] stated that the patients with tumors associated with lymphocytic response at the advancing edges have better survival as compared to the tumors lacking it. So as the intensity of associated lymphocytic response increases, better will be its prognosis.…”
Section: Resultsmentioning
confidence: 99%
“…The observation that a severe intratumoral inflammatory reaction, mostly lymphocytic and eosinophilic infiltration, is associated with a better survival in colorectal cancer has also been reported by others (Watt and House, 1978;Nacopoulou et al, 1981;Pretlow et al, 1983;Ponz de Leon et al, 1992). The inflammatory response within these malignancies could be considered as an attempt of the host to enclose the carcinomatous tissue and to destroy cancer cells.…”
Section: Discussionmentioning
confidence: 99%